157k views
2 votes
Multiply

show your work

2(2+3) 4x(x+2)
----------- × -------------
x(x-1) 10(x+3)​

1 Answer

4 votes

Answer:

The product of given two fractions is


(4(x+2))/((x-1)(x+3))

Therefore
(2(2+3))/(x(x-1))* (4x(x+2))/(10(x+3))=(4(x+2))/((x-1)(x+3))

Explanation:

Given expression is


(2(2+3))/(x(x-1))* (4x(x+2))/(10(x+3))

To find the product of two given fractions as below :


(2(2+3))/(x(x-1))* (4x(x+2))/(10(x+3))=(2(5))/(x(x-1))* (2x(x+2))/(5(x+3))


=(10)/(x(x-1))* (2x(x+2))/(5(x+3))


=(20x(x+2))/(5x(x-1)(x+3))


=(20x^2+40x)/((5x^2-5x)(x+3)) (multiply each term in the factor to each term in the another factor )


=(20x^2+40x)/(5x^3+15x^2-5x^2-15x) ( adding the like terms )


=(20x^2+40x)/(5x^3+10x^2-15x)


=(5x(4x+8))/(5x(x^2+2x-3))


=(4(x+2))/((x-1)(x+3))

Therefore
(2(2+3))/(x(x-1))* (4x(x+2))/(10(x+3))=(4(x+2))/((x-1)(x+3))

Therefore the product of given two fractions is
(4(x+2))/((x-1)(x+3))

User Moudy
by
4.7k points